2002
DOI: 10.1021/jf020352k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Free Radicals in Soluble Coffee by Electron Paramagnetic Resonance Spectroscopy

Abstract: EPR spectra of soluble coffee display single-line free radical signals in both the solid state and aqueous solution, along with signals from the paramagnetic ions Fe(III) and Mn(II). The intensity of the free radical signal in the pure solid was estimated to be ca. 7.5 x 10(16) unpaired electrons/g, and there was no significant change on dissolution in water. In aqueous solutions, however, the free radical signal declined rapidly over ca. 10-15 min in the temperature range 20-65 degrees C, after which only slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
4
25
1
Order By: Relevance
“…Decreases in EPR free radical signal intensities have also been observed during the storage of coffee concentrates , and this decrease was faster if O 2 was present in the extracting water, than if it was absent. In contrast to these observations, the results of Pascual et al (2002) indicate free radical formation in coffee solutions heated in air, and also that this increases with increasing temperature. The generation of this latter radical seems to correlate roughly with the pro-oxidant activity of coffee, as measured by its ability to destabilize ascorbic acid to produce the ascorbate radical.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Decreases in EPR free radical signal intensities have also been observed during the storage of coffee concentrates , and this decrease was faster if O 2 was present in the extracting water, than if it was absent. In contrast to these observations, the results of Pascual et al (2002) indicate free radical formation in coffee solutions heated in air, and also that this increases with increasing temperature. The generation of this latter radical seems to correlate roughly with the pro-oxidant activity of coffee, as measured by its ability to destabilize ascorbic acid to produce the ascorbate radical.…”
Section: Discussioncontrasting
confidence: 67%
“…The free radicals trapped in the measurements shown in Figure 68.4 are not those responsible for the temperature-dependent single peak signal in Figure 68.3. This was demonstrated by Pascual et al (2002), who showed that the single peak resonance is present along with that from the adduct, and as shown in Figure 68.5, its intensity is virtually identical to that seen in the absence of the spin trap.…”
Section: Role Of O 2 In the Free Radical Chemistry Of Coffee Solutionsmentioning
confidence: 69%
See 3 more Smart Citations